(untitled) (Jurnal Agribisnis dan Agrowisata, 2025)
The Role of Sari Jahe Mas Farmer Group in Tiga Village on Increasing the Income of Its Member Group. The Sari Jahe Mas farmer group is a farmer group in Tiga Village whose members are ginger farmers. In 2022, the price of ginger decreased compared to 2021. The decreased price of ginger is due to the high stock in the market and reduced market demand for ginger. This issues affect the income of farmer group members. This study aims to determine the role of Sari Jahe Mas farmer group in increasing income of its members, ginger farming income of group members, and the difference in income before and after joining the farmer group. The research sample is all members of the Sari Jahe Mas farmer group using quantitative descriptive analysis method. The results showed that the role of Sari Jahe Mas farmer group was classified as contributing with an average percentage score of 75.25% and the paired sample t test results showed a significant difference in the income level of group members before and after joining the farmer group. So with these results, farmer groups are advised to maintain farmer groups and form a farmer cooperative. In addition, for further researchers to conduct further research related to ginger marketing strategies and channels in the Sari Jahe Mas farmer group.